Strategies to upgrade animal health delivery in village poultry systems: Perspectives of stakeholders from northern Ghana and central zones in Tanzania - Enahoro, Dolapo K.; Galiè, Alessandra; Abukari, Y.; Chiwanga, G.H.; Kelly, T.R.; Kahamba, J.; Massawe, F.A.; Mapunda, F.; Jumba, Humphrey; Weber, Christoph; Dione, Michel M.; Kayang, B.; et al. (Frontiers Media, 2021)
Village chicken production holds much potential for the alleviation of malnutrition and poverty in rural communities in Africa. Owing to their subsistence nature, however, such systems are rife with infectious poultry diseases such as Newcastle disease (ND). Strategies common for the management of ND and other poultry diseases in intensive production systems, including vaccination and biosecurity measures, have seen limited success in the village production systems. New approaches are needed that can successfully deliver animal health inputs and services for the effective management of poultry health challenges in low-input systems. Our study utilized focus group discussions with men and women farmers as well as other poultry value chain actors such as input suppliers, live bird traders and processed poultry meat retailers, to investigate potential options for delivery of animal health care to village poultry systems in northern Ghana and central Tanzania. ND was commonly reported as a major disease constraint in the study sites of the two countries, with resulting fatalities particularly impactful on men and women producers and on traders. We therefore also conducted interviews that focused specifically on the gender component of village chicken production. The key health related challenges prioritized by women and men participants included limited access to, and poor quality of, vaccines and veterinary drugs, a shortage of veterinary officers, and insufficient knowledge and training of farmers on flock management practices. Women, more than men, emphasized the difficulties of accessing poultry health services. Our assessments suggest that for poultry health care delivery in the studied communities to be effective, there is need to improve the supply of good quality drugs and vaccines in rural areas, respond to the needs of both men and women, and recognize the different incentives for farmers, traders and other value chain actors. Community-based approaches and increased use of ICT technology such as mobile phones have much to offer in this regard.